The Concept of the Integration of Knowledge and Ablution in Islamic Education from Az-Zarnuji’s Perspective (An Analysis of the Book Ta’lim al-Muta’allim) - Siti Aisyah; Kustiana Arisanti; Ramdan Wagianto (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Islamic education essentially does not only emphasize the process of transferring knowledge, but also prioritizes the formation of spirituality, morality, and the blessing (barakah) of knowledge. However, contemporary educational systems tend to prioritize cognitive achievement over spiritual and moral dimensions, resulting in the decline of ethical orientation and religious values in educational practices. This study aims to analyze the concept of the integration of knowledge and ablution (wudhu) in Islamic education from the perspective of Shaykh Burhanuddin Az-Zarnuji through an analysis of the book Ta’lim al-Muta’allim and its relevance to contemporary Islamic education. This study employs a qualitative approach using a library research method. Primary data were obtained from the book Ta’lim al-Muta’allim, while secondary data were collected from scientific journals, books, and relevant studies published between 2020–2025. Data analysis was conducted through content analysis and a hermeneutic approach to examine the philosophical dimensions of Az-Zarnuji’s educational thought. The findings indicate that the integration of knowledge and ablution in Az-Zarnuji’s perspective is not merely related to ritual worship practices, but also represents a holistic integration between intellectual development, spiritual purification, and character formation (adab). Ablution is understood as a medium of outward and inward purification that prepares students to acquire beneficial and blessed knowledge. This study also demonstrates that Az-Zarnuji’s educational thought remains relevant in addressing the challenges of contemporary education, particularly moral degradation, educational pragmatism, and the weakening spirituality of students in the digital era. Therefore, the integration of knowledge and ablution can serve as a holistic and humanistic paradigm of Islamic education by emphasizing the balance between intellectual, spiritual, and moral dimensions.